Recent seismicity rate forecast for North East India: An approach based on rate state friction law. (1st May 2019) - Pandey, Auchitya Kumar; Chingtham, Prasanta; Prajapati, Sanjay K.; Roy, P.N.S.; Gupta, A.K.
Graphical abstract: Highlights: The rate and state friction law implemented for northeast region India. Forecasted seismicity rates are computed over MW ≥ 5 earthquake events during 2013–2015. Parameters calculated for every zones like the stress change, b -value, background seismicity rate. Stability for forecasted CSEP model seismicity data done by the N-test, L-test and M-test. Abstract: In this study, we have investigated the association of stress-field disparities through earthquake production rate in both spatially and temporally for Northeast region of India. Here, we have implemented the rate and state dependent friction law for forecasting the seismicity rate over MW ≥ 5.0 earthquake events during the period 2013–2015. The most valuable input model parameter of forecasting seismicity rate is Coulomb stresses changes (Δ CFF ), which promote the seismicity rate. The Δ CFF distributions that exhibit significant stress increase in the close proximity of the mainshock sources are found to be diminished with the inverse of the distance from the fault rupture plane. Basically, background seismicity depends on the Coulomb stress changes. These Coulomb stress changes amplify the background seismicity, so a little change in stress can produce very low or high seismicity rate in areas of high ambient seismicity. In several zones the high seismicity rate is revealed by the dominancy of the low b -value. The observed background seismicity rate lies between the ranges of 0–4.0. The significant b -value is achieved in the range of 0.57–1.54 along with average value of 0.93. We have taken the value of constant consecutive parameters (i.e. Aσ = 0.05 MPa) and constant effective friction coefficient of μ ' = 0.4 for all the faults. However, in the forecast model we have obtained the stress perturbations and heterogeneous b -value to infer the reliable result in comparison to reference forecast model for the period of 1963–2012. In this study, we have also adopted the RELM experiment in CSEP testing Centre to verify the consistency of the result related to forecast for the duration of 2013–2015. The statistical test provided the satisfactory result for this study region.